(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Syafitri WA, Ningsih F, Setyaningsih PP, Rachmania MK, Sari DCAF, Yabe S, Yokota A, Oetari A, Sjamsuridzal W. 2019. Screening for amylolytic activity and characterization of thermophilic Actinobacteria isolated from a geothermal area in West Java, Indonesia. Biodiversitas 20: 1929-1938. In this study, we describe the screening for amylolytic activity of 17 thermophilic Actinobacteria isolates obtained from the soil of Cisolok geysers, a geothermal area in West Java, Indonesia. All isolates were screened for amylolytic activity by the starch-agar plate method at various temperatures. The results showed that all of isolates were able to grow at 45oC. The growth abilities of the isolates grown in ISP 1 medium varied at temperatures from 45 to 60oC. Fifteen of the 17 isolates showed amylolytic activity at 45oC, 13 showed such activity at 50oC, and four showed activity at 55oC. Only three isolates, designated SL1-2-R-2, SL1-2-R-3, and SL1-2-R-4, showed growth and amylolytic activity at 60oC. These three isolates were selected for molecular identification. The nearly full-length of 16S rRNA gene sequences data showed that these three isolates have a similarity of 99.93-100% with Actinomadura keratinilytica WCC-2265T and of 98.74-98.91% with A. miaoliensis BC 44T-5T. Phylogenetic tree shows that all three isolates are clustered together in a monophyletic group with the type strain of A. keratinilytica WCC-2265T as their most closely related species, with 100% bootstrap support. Based on sequencing of the 16S rRNA gene, phylogenetic comparison, and phenotypic characterization, the three isolates were identified as A. keratinilytica.